INTERPRETATION OF THE IMAGE OF LATGALE IN THE CULTURE DISCOURSE - Senkāne, Olga (Via Latgalica, 2013)
There are cultures that focus on their origins, while there are also cultures oriented towards their destination: the former perceive the time in mythical manner – in its cycles, while the latter perceive it historically– in its linearity. The movement in the time-space continuum and its specifi cs in different cultures is provided by the desire either to pay more attention to the truth already known (the old texts) or to discover new one (new texts). The culture of Latgale is characterised by the prevalence of the old, constant texts or the traditional coding, as attested by persistent invoking of the region’s stereotypical values in the interpretations of the image of Latgale in literature, also the most operative genre of it – poetry. Nevertheless the artistic perception of Latgale in the poetry of the second half of the XX and the beginning of the XXI century shows not only respect towards the old, constant texts, but also intensive generation of new texts in certain periods of development of the regional culture. A very important indicator for identification of either the static or the dynamic culture type in artistic texts is the time: figurative perception of the past, the present and the future. The aim of the present study is to characterise the interpretation of the image of Latgale in the Latgalian patriotic poetry (the second half of the XX and the beginning of the XXI century). The image of Latgale is analysed in the culture discourse, based on the methods of cultural semiotics and phenomenology in treatment of time as well as the opposition of the new and the old. The present study uses as its source the Latgalian traditional (Romualds Spaitāns, Antons Rupainis, Antons Zvīdris, Marija Andžāne, Andris Vējāns, Pēteris Jurciņš, Marta Bārbale, Jānis Gurgons, Augusts Eglājs u. c.) and the modernist (Osvalds Kravaļs, Vilis Dzērvinīks, Antons Kūkojs, Ingrīda Tārauda u. c.) poetry. The semiotician Yuri Lotman lists the most important communicative functions of a text: 1) Information of an addressee; 2) Maintenance of collective cultural memory (in the format of inclusive transcendental abstraction archetype images, concepts, etc.); 3) Inclusion in a certain culture context (coding while respecting the traditions, stereotypical concepts, for the sake of cliché-like comprehensibility, recognisability); 4) Urge for the addressee’s self-examination (direct individual examination of the world’s phenomena and creation of codes). Realisation of the aforementioned functions in Latgalian poetry texts revealing the image of Latgale is clearly indicative of the rules of coding. First, the repeated denotation of abstraction representing and supporting the collective culture memory, its semantics and connotation depends upon the prioritised values of the respective age and society: Latgale as a land (the territorial identity) – territory or a region of a state and Latgale as people (the ethnic identity) – population or nation, part of a nation; second, inclusion into the region’s culture context is related to a wide though variation-less use of stereotypes (symbols, metaphors, rituals) and clichés; third, generation of new codes can nearly only be found in the modernist texts, where the priority is the revelation of direct impressions in formation of both the space-time continuum and the images, though also here in most cases direct impression in the poetry text functions as a projection of the past, a reconstruction (Latgale as the birthplace with the actualisation of place names – including the names of castle mounds, etc. in nostalgic retrospection). The image of Latgale in the coding system of the territorial identity is mainly marked with the cipher of concept "homeland” and in most cases overlaps with the ethnic identity codes, as it nearly always contains some stable and self-explanatory metonymic connection between the land and its inhabitants. In the Latgalian poetry it is related with the following semantically and stylistically expressive interpretations: 1) The protector – the potential/existing member of a family (a bride, a mother) or the one to be protected (an orphan left without the family, the youngest sister), such a connotation is mainly characteristic for allegorical national romanticism and national patriotic neoclassicism texts; 2) The sufferer (pain, a tear on a cheek, etc.); 3) The guardian of ethic values (sweat, conscience, etc.); 4) A birthplace with an accent on belonging (the poetical “I” admits his/her Latgale origin, frequently involving a particular set of place-names, using the reminiscence of the return of the prodigal son, with a shade of guilt in subtext; 5) A chosen, special place – most frequently in analogy /comparison structures as a reminiscence of the Latgalian mythology, folklore: a princess, a legend, soul, Muorys zeme (‘the Land of Māra’), Trešō zvaigzne (‘the Third Star’); also a figurative depiction of particularity of the territory and its inhabitants with the use of positive stereotypes: the land of the blue lakes, the green forests, people with an authentic material culture (castle-mounds, ceramics, linens), a language of their own and their specific religion (temples), hospitable, cordial people, ethnically diverse environment, et c., frequently in opposition ”centre – periphery”, ”the civilised – the natural”; 6) Vital and tough inhabitants.